Technology mediated communication as the basis for improving the end result of the Educational Inspection: the 2016/2017 Inspection Plan for Andalusia - Romero García, Manuel Ángel (Avances en Supervisión Educativa, 2017)
This article aims at analyzing the framework inside which the Educational Inspection of Andalusia implements communication routines. For this purpose, we will briefly describe the normative framework which regulates the processes of organization, management and, thereby, communication in the Educational Inspection of Andalusia. Then, the concept of competence will be revised, making special reference to those professional competences which must be developed by the Inspection in the fulfillment of its duties, and especially so, those linked to communication routines. Later, we will summarize the main actions implementing the current Inspection Plan for Andalusia, as well as the technological resources called for and their influence in the working processes of the staff of the Educational Inspection. Finally, a review on the proposals for the Training Plan for the Andalusian Inspection will be carried out, and a number of implications and conclusions will be put forward.
Keywords: educational inspection; educational platforms; ICTs; networking; collaborative working; professional competences